The Forgotten Work of Cultural Workers - Bischoping, Katherine; King, Adam D. K. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
This paper is based on work history interviews with a group of nine Toronto theatre workers covering a three-year period. During the interviews, participants did not spontaneously mention 13.1 per cent of their jobs in the creative cultural sector. Because forgotten work fails to register in surveys attempting to assess cultural workers’ contributions to the economy or to ameliorate their precarious conditions, it is important to explore why and how such work could go unreported. We locate the forgetting of cultural work in relation to the complexity and stresses of cultural workers’ schedules and to a discourse that opposes a devotion to art to the pursuit of money. Further, we explore how the participants’ particular tendency to forget their shortest-term jobs is informed by another discourse that prioritizes the building of a goals-based, coherent résumé. Last, we suggest that their surprising propensity to also forget their longest-term jobs can be understood in reference to the “piecework” model of cultural work and to a lack of socially supported remembering strategies. Based on these findings, we recommend improvements to the design of surveys on cultural workers’ work history.